Dendritic cell immunobiology and potential roles in immunotherapy - Fadilah, S.A.W.; Cheong, S.K. (College of Pathologists, Academy of Medicine Malaysia, 2007)
Owing to the importance of dendritic cells (DC) in the induction and control of immunity, an understanding of their biology is central to the development of potent immunotherapies for cancer, chronic infections, autoimmune disease, and induction of transplantation tolerance. This review surveys the heterogeneity of DC with regards to their phenotype and developmental origin, and how they initiate, modify and regulate the immune response, with emphasis on their maturation, migration, antigen-presentation and interaction with T cells and other immune cells. Much of this knowledge is obtained through research on murine DC. Research on human DC has been hampered by limitations associated with in vitro assays and limited access to human tissues. New approaches on human DC research are required in order to develop novel strategies for the treatment of microbial infections, the control of graft rejection, and the improvement of DC-based immunotherapeutic protocols for autoimmunity, allergy, and cancer.